Autologous Human Immunocompetent White Adipose Tissue‐on‐Chip. Issue 18 (24th April 2022) - Rogal, Julia; Roosz, Julia; Teufel, Claudia; Cipriano, Madalena; Xu, Raylin; Eisler, Wiebke; Weiss, Martin; Schenke‐Layland, Katja; Loskill, Peter
Abstract: Obesity and associated diseases, such as diabetes, have reached epidemic proportions globally. In this era of "diabesity", white adipose tissue (WAT) has become a target of high interest for therapeutic strategies. To gain insights into mechanisms of adipose (patho‐)physiology, researchers traditionally relied on animal models. Leveraging Organ‐on‐Chip technology, a microphysiological in vitro model of human WAT is introduced: a tailored microfluidic platform featuring vasculature‐like perfusion that integrates 3D tissues comprising all major WAT‐associated cellular components (mature adipocytes, organotypic endothelial barriers, stromovascular cells including adipose tissue macrophages) in an autologous manner and recapitulates pivotal WAT functions, such as energy storage and mobilization as well as endocrine and immunomodulatory activities. A precisely controllable bottom‐up approach enables the generation of a multitude of replicates per donor circumventing inter‐donor variability issues and paving the way for personalized medicine. Moreover, it allows to adjust the model's degree of complexity via a flexible mix‐and‐match approach. This WAT‐on‐Chip system constitutes the first human‐based, autologous, and immunocompetent in vitro adipose tissue model that recapitulates almost full tissue heterogeneity and can become a powerful tool for human‐relevant research in the field of metabolism and its associated diseases as well as for compound testing and personalized‐ and precision medicine applications. Abstract : In the era of "diabesity", human adipose tissue research has become more important than ever. However, a lack of predictive model systems has traditionally impaired progress in this field. A human, patient‐specific, immunocompetent white adipose tissue (WAT)‐on‐chip system is developed, which integrates virtually all WAT‐associated cell types and reliably reflects in vivo WAT functions in vitro.